EDUKASI MASYARAKAT AWAM PENGURUS GEREJA DALAM RANGKA MENINGKATKAN “STROKE AWARNESS” DI KOTA JAYAPURA - Bolly, Hendrikus Masang Ban; Sulelino, Renny; Sitanggang, Prysta Aderlia (Jurnal Media Tropika, 2024)
A stroke is an acute attack due to blockage or rupture of blood vessels in the brain. Negligence and delay in fast and appropriate treatment will increase the death rate and permanent disability in patients with stroke. Education for promotive and preventive purposes related to stroke for church administrators is critical considering their roles and functions. This "stroke awareness" educational activity aims to provide knowledge (cognitive) and initial skills for stroke patient caregivers, as well as containing promotive and preventive content to improve brain health. The implementation method is interactive in-house training including material delivery, video sessions, and simple simulations. The activity was implemented in two Catholic churches in Jayapura City attended by 43 church administrators, and the training duration of around 150 minutes. This activity is crucial to provide basic knowledge about all aspects of stroke, starting from the causes, risk factors, course of the disease, complications, treatment, and estimated patient outcomes as well as tips and tricks for maintaining brain health. The simulations include recognizing early symptoms, initial skill in management of the patients at the scene and transferring patients to the hospital. Educational activities like this are recognized as very beneficial and are recommended to be carried out routinely to reach all people. Public education related to non-infectious diseases such as stroke which statistically tends to increase currently needs to be done routinely to improve the health of the community. The church can be a potential target for activating healthy lifestyles and reducing the risk of stroke in the community.